Computer Viruses and Challenges for Anti-virus Industry (International Journal of Engineering and Computer Science, 2014)
In today’s world every organizations and individuals using computer and internet need to have a wide-ranging virus protection policy to combat the growing threats of computer viruses by means of anti-virus. The anti-virus approach consists of waiting for a number of computers to be infected, detecting the virus, designing a solution, and delivering and deploying the solution. In this situation, it is very difficult to prevent every machine from being compromised by virus. This paper highlights the most common virus types and their modus operandi. Further it is also discussed that in present scenario due to the evolution of new viruses every day why it is very difficult for Anti-virus industry to make themselves up-to-date each day as per the definition of new emerging viruses.